A Systematic Review of Gamification-Based Learning Resources in Civic Education: Enhancing Student Engagement and Civic Competence - Hanifah, Hanifah; Nengah Suastika, I; Bagus Sanjaya, Dewa (Jurnal Profesi Pendidikan, 2025)
This study conducted a systematic review of gamification-based learning resources in elementary school Civics Education (PKn) to improve student engagement and civic competence. The Systematic Literature Review (SLR) method, with the PRISMA framework, was used to analyse 17 empirical studies published between 2019 and 2024. The results showed that gamification significantly improved student motivation (86% of studies), collaborative skills (72%), and civic understanding (68%) through elements such as badges, leaderboards, and interactive simulations. Key success factors include alignment with the curriculum, teacher training, and cultural relevance. In Indonesia, implementation challenges include limited digital infrastructure, as only 35% of rural schools have stable internet access, and teacher readiness is not yet optimal. This study proposes a contextual gamification approach that integrates local values ​​such as cooperation and low-tech solutions to overcome these obstacles. Key findings indicate that gamification is not only a motivational tool but also an effective pedagogical strategy for developing holistic civic competence. Policy recommendations include ongoing teacher training, development of inclusive implementation guidelines, and longitudinal research to measure long-term impacts. In conclusion, gamification designed with local context and infrastructure limitations in mind can be a sustainable solution to revitalise civic learning in Indonesia.